Pertumbuhan dan Frekuensi Panen Tanaman Cabai Merah pada Kondisi Suboptimal secara Terapung - Susilawati Susilawati; Muhammad Ammar; Irmawati Irmawati; Muhammad Umar Harun; Erizal Sodikin; Budiyati Ichwan (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[GROWTH AND HARVESTING FREQUENCY OF RED CHILI PLANTS WITH THE APPLICATION OF  NPK FERTILIZERS CULTIVATED ON SUB-OPTIMAL LAND IN FLOATING CULTURE SYSTEM]. The low productivity of red chili in South Sumatra is mostly due to its cultivation was conducted in sub-optimal land that is less favorable for producing vegetable crops. This study aimed to evaluate growth and yield of red chili plants under suboptimal conditions using various doses of NPK fertilizer. The experiment was carried out from June to October 2022, at the water reservoir and experimental field (as a comparison) at the Faculty of Agriculture Universitas Sriwijaya, Indralaya, South Sumatra with an altitude of 10 m above sea level. Both experiments were arranged in a randomized block design with three replications and one factor in the group, namely NPK fertilizer doses (0, 5, 10, and 15 g/polybag). For the experiment in the water reservoir, each treatment was arranged randomly in a 200 cm x 100 cm bamboo raft (for each group). The results showed that the application of NPK fertilizer in floating cultivation did not increase plant height, number of leaves, shoot diameter, and harvesting frequency of red chili. It was concluded that the application of NPK fertilizer in floating cultivation did not increase growth and harvesting frequency of red chili.